Novel Strategies for the Treatment of Chondrosarcomas: Targeting Integrins. (30th December 2013) - Chen, Jui-Chieh; Fong, Yi-Chin; Tang, Chih-Hsin
Abstract : Chondrosarcomas are a heterogeneous group of malignant bone tumors that are characterized by the production of cartilaginous extracellular matrix. They are the second most frequently occurring type of bone malignancy. Surgical resection remains the primary mode of treatment for chondrosarcomas, since conventional chemotherapy and radiotherapy are largely ineffective. Treatment of patients with high-grade chondrosarcomas is particularly challenging, owing to the lack of effective adjuvant therapies. Integrins are cell surface adhesion molecules that regulate a variety of cellular functions. They have been implicated in the initiation, progression, and metastasis of solid tumors. Deregulation of integrin expression and/or signaling has been identified in many chondrosarcomas. Therefore, the development of new drugs that can selectively target regulators of integrin gene expression and ligand-integrin signaling might hold great promise for the treatment of these cancers. In this review, we provide an overview of the current understanding of how growth factors, chemokines/cytokines, and other inflammation-related molecules can control the expression of specific integrins to promote cell migration. We also review the roles of specific subtypes of integrins and their signaling mechanisms, and discuss how these might be involved in tumor growth and metastasis. Finally, novel therapeutic strategies for targeting these molecules will be discussed.